Integration of parafoveal orthographic information during foveal word reading: beyond the sub-lexical level?. Issue 10 (3rd October 2017) - Snell, Joshua; Vitu, Françoise; Grainger, Jonathan
ABSTRACT: Prior research has shown that processing of a given target word is facilitated by the simultaneous presentation of orthographically related stimuli in the parafovea. Here we investigate the nature of such spatial integration processes by presenting orthographic neighbours of target words in the parafovea, considering that neighbours have been shown to inhibit, rather than facilitate, recognition of target words in foveal masked priming research. In Experiment 1, we used the gaze-contingent boundary paradigm to manipulate the parafoveal information subjects received while they fixated a target word within a sentence. In Experiment 2, we used the Flanking Letters Lexical Decision paradigm to manipulate parafoveal information while subjects read isolated words. Parafoveal words were either a higher-frequency orthographic neighbour of targets words (e.g., blue-blur ) or a high-frequency unrelated word (e.g., hand-blur ). We found that parafoveal orthographic neighbours facilitated, rather than inhibited, processing of the target. Thus, the present findings provide further evidence that orthographic information is integrated across multiple words and suggest that either the integration process does not enable simultaneous access to those words' lexical representations, or that lexical representations activated by spatially distinct stimuli do not compete for recognition.